POSSIBILITIES OF OPTIMAL ALGORITHMS FOR INTERNET OF THINGS NETWORK (International Scientific Journal Alfraganus, 2025)
The article outlines the features of working with Internet of Things sensor networks as a monitoring infrastructure for continuous objects. It describes basic approaches to improve the accuracy and energy efficiency of these types of systems. A method for optimizing algorithms for determining the boundaries of continuous objects in the Internet of Things network is proposed. This approach is based on classifying regions around boundary nodes and subregions with low probability of events. The results show that optimization of the hungry algorithm can be used to activate a certain number of neighboring nodes in relevant sub-areas of the IoT network. Thus, this approach makes it possible to clarify the boundaries of objects using data from activated sensors of Internet of Things network nodes. In addition, the text builds a mathematical model that gives better object detection accuracy with less load on the hardware platform. If you need to correct plagiarism in this text, it is recommended to rephrase and rework the sentences, add your unique content and links to sources of information.
Keywords: Internet of Things; sensor networks; edge detection; greedy algorithms